Influence of the nature of metal-containing polymer-silicate filler on the physico-mechanical properties of polypropylene - Masyuk, Andrii; Paraschak, Oleksandr; Levytskyi, Volodymyr (Видавництво Львівської політехніки, 2017)
The influence of Ni-containing polymer-silicate filler modified by polyvinyl alcohol on the physico-mechanical (surface hardness, strength at breaking, elastic modulus, coefficient of structure) properties of thermoplastic composites based on polypropylene has been found.
Keywords: metal-containing polymer-silicate fillers; polypropylene; physico -mechanical properties